The Government's Persuasive Communication Strategy in Preventing the Spread of the Covid-19 Virus in Indonesia - Amin Amin (Jurnal EduHealth, 2023)
Campaigning for health protocols is a very difficult thing, especially in making people aware, especially during this pandemic era. So the government as the party most responsible for handling the spread of the Covid-19 virus must determine strategic steps so that all programs and messages to be conveyed can be well received by all elements of society. Basically, communication is the most important part in dealing with the threat of a pandemic, because public trust needs to be built and maintained so that panic and excess misunderstandings do not occur. One of the instructions given by the president to the government is that the government must show its seriousness, especially in handling this situation and build an ideal communication through comprehensive and regular explanations, by explaining what the government has done and will do. The persuasive approach formed by the government is aimed at campaigning for health protocols in the community and is designed in such a way that the target can accept it consciously and without coercion, which is based on three main dimensions, namely the process of forming a response, the process of strengthening the response, the process of changing the response. On the other hand, a persuasive communication strategy will actually create two-way (reciprocal) communication by disseminating information from the organization to the public that is educational and enlightening, as well as by taking a persuasive approach, so as to create mutual understanding, respect and understanding.